Research trends in mining accidents study: A systematic literature review - Siti Noraishah, Ismail; Azizan, Ramli; Hanida, Abdul Aziz (Elsevier, 2021)
Mining is well known as a high-risk industry with high accident rates. However, there is a scarcity of material that aims to investigate and understand the research trends in mining accidents and the current scenarios related to this topic. Therefore, the objective of this systematic review was to investigate the research trends in mining accidents. By applying a Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) review method, a systematic literature review (SLR) identified 57 studies related to mining accident issues from 2015 to 2019 from the Science Direct and Scopus databases. Based on these 57 studies, four main themes were developed: the main causes of mining accidents (46%), the prevention of mining accidents (20%), and the challenges of (17%) and impacts of post-mining accidents (17%). The four themes produced a total of 35 sub-themes. Mechanical failure was identified as the main cause of mining accidents and the application of software or safety models is essential to minimize the number of mining accidents. Mine owners have the responsibility to provide a safe working environment for mine workers, and face substantial challenges to achieve this. Moreover, the impact of post-mining accidents led to adverse impacts on the environment. This systematic review study aims to assist mine owners by providing a better understanding of mining accident issues. The study also addresses miners, government and policymakers so all groups can collectively target the reduction of mining accidents in the future